Utilization of Whey Protein Isolate as CO2 Foam Stabilizer for Enhanced Oil Recovery - Mohamed Sasi Said; Mohd Zaidi Jaafar; Shaziera Omar; Ali Mohamed Samin (ASEAN Journal of Chemical Engineering, 2022)
Understanding the fundamental aspects of foaming properties will influence its generation and stabilization at different concentrations of the critical aggregation concentration (CAC), foam volume stability, foam height, salinity influences, and crude oil CO2-foam stability. Carbon-Dioxide based enhanced oil recovery techniques are widely employed to extract additional oil from the reservoir. The adsorption of protein at the interfaces produces extremely viscoelastic layers with high viscosity. This research aims to investigate whether whey protein isolate (WPI) is a foaming agent that can be used to improve oil recovery. WPI lowers the interfaces’ surface tension, which also has a propensity to disclose and stabilize the interface by forming a viscoelastic network and directing to high surface moduli. Comparatively, the surface tension is lowered by sodium dodecyl sulfate (SDS) surfactants than the WPI, but they do not produce a high modulus interface. WPI is demonstrated to be a greater foam stabilizer in oil and various salt conditions than SDS foam. Adding sodium chloride (NaCl) increased the half-life and volume of foam more on WPI foam compared to SDS foam. SDS foamability and foam consistency decreased dramatically at 2 wt% of NaCl concentration and above while WPI foam increased. The crude oil affected both foams, but WPI foam has not been affected as much as the SDS foam due to its high strength compared to traditional foams. The study shows that WPI reduced interfacial tension from 38 to 11 mN/m and reduced surface tension (72.3 to 48 mN/m). It was low enough and can be used as a substitute for a foaming agent to enhance the recovery of oil.